LIMIT EQUILIBRIUM CONDITIONS APPROACH IN ANALYSIS OF DOWNSTREAM LEFT-BANK LANDSLIDE OF JATIGEDE DAM-SITE, SUMEDANG DISTRICT, WEST JAVA - HASIBUAN , GINDA
The problem of slope mass movements around the construction area of Jatigede dam has led to the disruption of construction activities and destruction of some existing facilities. In downstream left-bank area of the damsite, slope mass failure was occurred in rainy season with higly rainfall intensity in days before. Generally, research area has an undulating morphology with ground surface inclination as high as 400 in some location. This area is composed of relatively unconsolidated Quarternary volcanic breccia over the claystone with intercalation of sandstone in lower part. The topsoils of sandy silt to silty sand with moderately plastic to plastic is the products of rock weathering in this area, and contains gravels locally. The analyses conducted was based on limit equilibrium condition of static forces in slope mass. This method was combined with failure back-analysis, short-term analysis, and long-term analysis. In addition, rainfall characteristic analysis was used to analyze the slope mass failure in research area. Back-analysis result friction angle parameters at failure between 13.40 Ã‚Â– 15.40. Several factors that caused decreasing the stability from early condition known has varied influence. The historical earthquakes that give peak ground acceleration 0.014g to the area has contribution less than 28% to overall safety factor decreasing. The contribution from the increasing of groundwater level in slope mass is more than 70%. Tension cracks that appear pre-failure give its constribution less than 3.5%. Analysis of cummulative rainfall intensity shows the antecedent rainfall has been occurred since 30 days pre-failure. Critical rainfall intensity result 108 mm with antecedent intensity precondition as high as 650 mm. It indicated that a deep-seated failure type was occurred in relatively drained slope mass. Short-term stability analysis in research area shows some location in this area has a susceptibilty for mass movement. Long-term stability analysis shows that area has a high stability for condition with no groundwater level (dry season), relatively stable for condition with groundwater (rainy season), and no stable under both influence of groundwater and seismicity acceleration based on Indonesian Earthquake Hazard Map. From overall analyses, it can be stated that a regressive failure type could be occurred in the research area.